[en] LINGUISTIC ASPECTS OF CRIMINAL NORMS IN THE BRAZILIAN PENAL CODE - REGINA DE SOUZA FERREIRA LIMA DA SILVA (MAXWELL, 2003)
[pt] Empreende-se no trabalho a análise lingüística do texto legal-penal, com base nas normas penais incriminadoras contidas no Código Penal Brasileiro, buscando identificar as propriedades formais destas e ressaltando aspectos da estrutura sintática das mesmas e da semântica do desvalor nelas refletido. O estudo visa a refutar a idéia (extremamente difundida entre os penalistas) de que o verbo seria o elemento nuclear dos tipos penais. Isto é feito demonstrando-se que, muitas vezes, não é no verbo que reside o cerne do desvalor enfocado nas normas incriminadoras. Pois, se é fato que o desvalor de conduta se expressa notadamente por meio dele, o desvalor de resultado se concentra nos complementos verbais e/ou nos adjuntos na descrição do tipo. Assim sendo, o verbo, tomado isoladamente, é com freqüência insuficiente para caracterizar a ação/omissão humana desvalorada, particularmente quando o desvalor é predominantemente de resultado. Nesses casos, o verbo deve ser considerado em conjunto com seus complementos e com os adjuntos presentes no tipo, para se determinar o que a norma penal incriminadora pretende evitar/reprimir. Identificam-se nessa análise, quatro classes de verbos - os intrinsecamente negativos, os negativos moldáveis, os neutros e os positivos moldáveis. === [en] This work undertakes the linguistic analysis of the criminal law text based on the criminal norms comprised in the Brazilian Penal Code. It aims at identifying their formal properties and at stressing some aspects of the syntactic structure of such norms and of the semantics of the devalue (negative value) reflected in them. The study intends to refute the idea (largely spread among criminalists) that the verb is the nuclear element in the description of penal types. This is done by demonstrating that the devalue focused in criminal norms often does not dwell in the verb. For, if it is a fact that the devalued conduct is usually conveyed by the verb, the devalued result lies basically on verbal complements and on adjunctive phrases in the type description. Thus, the verb, taken by itself, is usually insufficient to characterize the devalued human action/omission, particularly when the devalue resides predominantly in its result. In such cases, in determining what exactly the criminal norm aims at avoiding/repressing, the verb must be taken into account in association with its complements and with the adjunctive expressions present in the type description. In this analysis, four verb classes are identified, namely those of intrinsically negative, adaptable negative, neutral and adaptable positive verbs.